Dari tegalan hingga pusat perekonomian industri: desa seduri, 1975-2019 - Ananda Surya Salsabila (Historiography: Journal of Indonesian History and Education, 2023)
Seduri Village itself was recorded in colonial government reports since the early 20th century as a village area dominated by moor areas, until 2018 it was noted that Seduri Village had 5 major industries and had the highest tax contribution out of 19 villages in Mojosari District. This paper attempts to narrate the development of one of the villages in Mojosari District, Mojokerto Regency, namely Seduri Village in the 1975-2019 period. The method used is the historical method by collecting literature from sources in the form of books, articles, archives of government reports and newspapers. This study shows that geographical conditions with sufficient land availability, strategic village location, population growth and the determination of Mojosari as the capital of Mojokerto Regency are the main factors in village development. These four things encouraged the development of the village, which was originally a moor area that developed into the economic center of Mojosari City.Desa Seduri sendiri tercatat dalam laporan-laporan pemerintah kolonial sejak awal abad ke-20 sebagai wilayah desa yang didominasi oleh kawasan tegalan, hingga tahun 2018 tercatat Desa Seduri memiliki 5 industri besar dan memiliki kontribusi pajak paling tinggi dari 19 desa di Kecamatan Mojosari. Tulisan ini berusaha menarasikan perkembangan salah satu desa di Kecamatan Mojosari Kabupaten Mojokerto yaitu Desa Seduri pada periode 1975-2019. Metode yang digunakan adalah metode sejarah dengan melakukan pengumpulan dan literatur pada sumber-sumber berupa buku, artikel, arsip laporan pemerintahan dan koran. Penelitian ini menunjukkan bahwa keadaan geografis dengan ketersediaan lahan yang cukup, lokasi desa yang strategis, pertumbuhan penduduk dan penentuan Mojosari sebagai ibukota Kabupaten Mojokerto menjadi faktor utama dalam perkembangan desa. Keempat hal tersebut mendorong perkembangan desa yang awalnya berupa wilayah tegalan berkembanag menjadi pusat perekonomian Kota Mojosari.